The Analysis of Product Placement on Brand Awareness and Brand Attitude of Kopiko Candy in Season 2 of Taxi Driver Korean Drama - Chalista Regina Br Nadeak; Rahmat Setiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research is conducted to analyze brand awareness and brand attitude of Kopiko candy affected by product placement of Kopiko product in the second season of Taxi Driver. There are three variables used in this research. Product placement was used as independent variable, while brand awareness and brand attitude acted as dependent variables. 181 respondents were chosen by purposive sampling method using specific criteria. Questionnaire as data collecting tools was filled by respondents from google form link sent by researcher. Data analysis method used was Structural Equation Modeling (SEM) with AMOS 24 as the tools. Results show that product placement of Kopiko candy impacts significantly towards both brand awareness and brand attitude of Kopiko brand. Meanwhile, brand awareness does not give significant effect towards brand attitude, hence it fails to act as mediator variable in this research.